Minor illness education for parents of young children. - Robbins, H; Hundley, V; Osman, L (2003)
BACKGROUND: A number of previous studies on minor illness have concentrated on nurse-led clinics and the role of nurse practitioners. This study examines the effect of a minor illness education programme which aimed to increase parents' confidence and knowledge in managing childhood illnesses. AIM: The primary aim of this study was to evaluate the effectiveness of a home visit and booklet in providing education to parents about minor infant illnesses. DESIGN: A randomized controlled trial was conducted. The intervention involved a home visit to discuss parents' concerns and provide advice and information, and a booklet advising parents what to do and when to consult about infant illnesses. METHOD: A total of 120 parents of 6 week old babies were identified over a 6 month period, using health visitors' caseloads, and randomized to an intervention group (60), that received a visit and a booklet, or a control group (60) that received standard care. Groups were compared on entry to the study and at 7 months, in terms of parental knowledge and confidence about childhood illnesses, the intended use of home care activities, intention to consult professionals and actual use of health services. Data were collected by self-completed questionnaire and case note review. FINDINGS: The educational intervention resulted in a reduction in visits to the child health clinic but had little effect on use of other services. Parents in the intervention group showed a general trend towards greater certainty about the home care options they would choose, and a reduction in intention to consult a doctor. However, they also indicated a feeling of reduced confidence and knowledge. CONCLUSION: The trial showed no effect on use of services but did demonstrate reduction in parents' intentions to consult a doctor, which appeared to be because of increased certainty about home care. However, it is of concern that they indicated feeling less confident and knowledgeable. It is not possible to clarify whether this represented anxiety that was constructive, enhancing decision-making or was destructive. Further work into the role of education in parental decision-making, anxiety levels and enhancement of confidence is required.